Oocyte and embryo culture under oil profoundly alters effective concentrations of small molecule inhibitors - Rémillard-Labrosse, Gaudeline; Cohen, Sydney; Boucher, Éliane; Gagnon, Kéryanne; Vasilev, Filip; Mihajlović, Aleksandar I.; FitzHarris, Greg (Frontiers in Cell and Developmental Biology, 2024)
Culture of oocytes and embryos in media under oil is a cornerstone of fertility treatment, and extensively employed in experimental investigation of early mammalian development. It has been noted anecdotally by some that certain small molecule inhibitors might lose activity in oil-covered culture systems, presumably by drug partitioning into the oil. Here we took a pseudo-pharmacological approach to appraise this formally using mouse oocytes and embryos. Using different culture dish designs with defined media:oil volume ratios, we show that the EC50 of the widely employed microtubule poison nocodazole shifts as a function of the media:oil ratio, such that nocodazole concentrations that prevent cell division in oil-free culture fail to in oil-covered media drops. Relatively subtle changes in culture dish design lead to measurable changes in EC50. This effect is not specific to one type of culture oil, and can be readily observed both in oocyte and embryo culture experiments. We subsequently applied a similar approach to a small panel of widely employed cell cycle-related inhibitors, finding that most lose activity in standard oil-covered oocyte/embryo culture systems. Our data suggest that loss of small molecule activity in oil-covered oocyte and embryo culture is a widespread phenomenon with potentially far-reaching implications for data reproducibility, and we recommend avoiding oil-covered culture for experiments employing inhibitors/drugs wherever possible.